2018
DOI: 10.2196/11640
|View full text |Cite
|
Sign up to set email alerts
|

Gamified Cognitive Bias Modification Interventions for Psychiatric Disorders: Review

Abstract: BackgroundAutomatic biases, such as attentional biases and avoidance and interpretative biases, have been purported to be responsible for several psychiatric disorders. Gamification has been considered for cognitive bias modification, mainly to address the core issues of diminishing motivation to train over time, as bias modification intervention tasks tend to be highly repetitive. While a prior review has suggested how gamification strategies could be applied to such tasks, there remains a lack of systematic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Multi-session studies combined with follow-up assessments allow for an investigation of the acceptability and effectiveness of the training in the long term. In doing so researchers should consider strategies for facilitating participant engagement with the training over time (Zhang et al, 2018) and to assess whether changes observed in interpretation biases are associated with changes in social perceptions and behaviors, as well as key clinical variables. It will also be important to explore potential pathways through which this training can be related to improvements in symptoms, such as through strengthening responsiveness to social acceptance or support.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-session studies combined with follow-up assessments allow for an investigation of the acceptability and effectiveness of the training in the long term. In doing so researchers should consider strategies for facilitating participant engagement with the training over time (Zhang et al, 2018) and to assess whether changes observed in interpretation biases are associated with changes in social perceptions and behaviors, as well as key clinical variables. It will also be important to explore potential pathways through which this training can be related to improvements in symptoms, such as through strengthening responsiveness to social acceptance or support.…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been investigations using serious games (games designed specifically for specific intervention) and gamification technologies to reduce the boredom associated with these interventions in the hope of reducing attrition. [14] in their review of gamified cognitive bias modification interventions, reported only two out of four interventions to be effective, and these two were for individuals with anxiety disorders. One of the studies, (Boendmarker et al (2016)) [33] reported there being no added effectiveness with the integration of gamification elements; despite their previous article suggesting various methods that gamification could be added onto a conventional task.…”
Section: Challenges Pertaining To Attrition and Motivation To Trainmentioning
confidence: 99%
“…While, [14] have in their review of mobile cognitive bias modification interventions highlighted the presence of a disconnect between academic and developers, it must be noted that most of the existing cognitive bias modification interventions have been conceptualized based on inputs from academics. There remains a lack of patient participation in the conceptualization process, so the intervention might not meet their needs or preferences.…”
Section: Challenges Pertaining To Evidence Base Of Cognitive Bias Modmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, many researchers have designed gamification-based applications to capture consumers’ fun and “gameful” experiences [ 9 ] and to observe weight loss in overweight and obese adolescents, which eventually improves their health conditions [ 12 ]. On the other hand, Zhang et al [ 17 ] used gamification for cognitive bias modification. Besides usage, usability of gamification is equally important as it enables users to perform tasks effectively and efficiently.…”
Section: Introductionmentioning
confidence: 99%